DEVELOPMENT OF THE METHODOLOGY FOR RESEARCHING THE ENVIRONMENT OF SOCIAL RESILIENCE OF THE POPULATION OF THE REGION - BILETSKA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to develop a methodology for researching the environment of social resilience of the population of the region. The study reveals the relevance of the problem of forming a methodology for analyzing socio-economic systems using the example of the environment of social resilience of the population, which is understood as the quality of the social system of the region in the sense of its ability to prevent the realization of human risks and threats that lead to a decrease in its social security. The methodology was developed to assess the social resilience of the population of the Carpathian region of Ukraine. To assess the environment of social resilience, 31 determinants were selected, grouped into four groups: (1) employment, income, living conditions, (2) social security, (3) social tension, (4) provision of social infrastructure. The author's research methodology involves the implementation of 5 stages: the formation of homogeneous dynamic data series; determination of dynamic weighting coefficients of indicators within each group; calculation of weighted coefficients of indicators; construction of weighted coefficients of subsystems (groups); construction of the integral coefficient of the medium.It is shown that the determining determinants of the social resilience of the regions are the system of indicators of socio-economic vulnerability of the population, the strengthening of which leads to the emergence of new and strengthening of current social risks and threats in different time periods. It is proved that social resilience, as opposed to social vulnerability, characterizes the measure of the ability of the population and its individual groups to independently satisfy their needs and realize their own social rights in the conditions that have develop. The scientific novelty of the research results lies in the further development of the methodology for analyzing complex socio-economic systems, in particular in the field of quality of life and strengthening the social resilience of the region's population.
Keywords: methodology of scientific research; social resilience; environment; quality of life; analysis technique; management